PARTISIPASI MASYARAKAT DALAM MENINGKATKAN MINAT KUNJUNG DESTINASI WISATA BUKIT KASIH DI DESA KANONANG KABUPATEN MINAHASA - Raymond Randy Rambe; Elfie Mingkid; Johny P. Lengkong; Novie R. Pioh; Maria H. Pratiknjo (Journal Publicuho, 2024)
This research aims at community participation in increasing interest in visiting the Bukit Kasih tourist destination in Kanonang Village, Minahasa Regency. The research method uses a qualitative approach, primary and secondary data sources through observation, interviews and document studies and uses interactive data analysis techniques according to Miles Huberman and Saldana (2014). The research results show that in increasing interest in visiting the Bukit Kasih tourist destination in Kanonang Village, the North Sulawesi Provincial Tourism Office has attempted to involve the community through outreach and training. However, the lack of coordination between the community, village government and related agencies is an obstacle. Even though the ability of the community to be involved is good, there is still a need to increase awareness and active involvement in tourism promotion and management. Apart from that, policies such as increasing entrance fees that are not approved by the public can reduce interest in visiting tourists. Therefore, maximum encouragement is needed to increase public awareness in participating and expressing opinions in the management of tourist destinations.